Exposure to alcohol and overall survival in head and neck cancer: A regional cohort study - Denissoff Alexander; Huusko Teemu; Ventela Sami; Niemela Solja; Routila Johannes (WILEY, 2025)
Background There is a paucity of knowledge regarding the association of alcohol use with overall survival (OS) of patients with head and neck squamous cell carcinoma (HNSCC).
Methods All 1033 patients treated for new HNSCC in Southwest Finland regional referral center of Turku University Hospital in 2005-2015. Cox regression analysis was used. Tumor TNM classification, age at baseline and tobacco smoking status were assessed as potential confounders.
Results A history of severe harmful alcohol use with major somatic complications (HR: 1.41; 95%CI: 1.06-1.87; p = 0.017) as well as current use of at least 10 units per week (HR: 1.44, 95%CI: 1.16-1.78; p = 0.001) were associated with OS.
Conclusions Alcohol consumption of 10-20 units/week, often regarded as moderate use, was found to increase risk of mortality independent of other prognostic variables. Systematic screening of risk level alcohol use and prognostic evaluation of alcohol brief intervention strategies is highly recommended.